Tanzania Meteorological Authority Stakeholders’ Training on the Sixth National Climate Outlook Forum (NCOF6) for November 2022 – April 2023 Rainfall Season - Recha, John W.M. (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
In the late 1990s the World Meteorological Organisation, National Meteorological and Hydrological Services (NMHSs), regional institutions and other international organizations initiated an innovative process known as the Regional Climate Outlook Forums, that led to the National Climate Outlook Forums. These Forums bring together climate experts, on an operational basis, to produce geographical climate outlooks based on input - climate predictions - from all participants. By bringing together the different experts, the Forums ensure consistency in the access to, and interpretation of, climate information. Through interaction with users in the key economic sectors, extension agencies and policymakers, the Forums assess the likely implications of the outlooks on the most pertinent socioeconomic sectors and explore the ways these outlooks could be used by them. The Tanzania Climate Outlook Forum focused on the delivery of consensus-based, userrelevant climate outlook product for the November 2022 – April 2023 (Msimu) rainfall season in real time through national cooperation and partnership with AICCRA (https://aiccra.cgiar.org/) and the International Livestock Research Institute.